Synthesis, characterization, quantum chemical calculations and evaluation of antioxidant properties of 1,3,4-thiadiazole derivatives including 2- and 3-methoxy cinnamic acids - Gür, Mahmut; Muğlu, Halit; Çavuş, M. Serdar; Güder, Aytaç; Sayıner, Hakan S.; Kandemirli, Fatma (Elsevier BV, 2017)
Abstract A series of 1,3,4-thiadiazole derivatives including 2- and 3-methoxy cinnamic acids were synthesized, and their structures were elucidated by the UV, IR, 1 H NMR, 13 C NMR spectroscopies and elemental analysis. The UV and IR calculations of the molecules were performed by using B3LYP, HF and MP2 methods with selected 6-311++G(2d,2p), 6-311++G(3df,3pd) and cc-pvtz basis sets. Dipole moment, polarizability, chemical hardness/softness and electronegativity were also calculated and analyzed. Experimental FT-IR spectra and UV–Vis spectrum of the compounds were compared with theoretical data. Furthermore, antioxidant activities of the compounds were practised via different test methods such as 2,2-diphenyl-1-picryl-hydrazyl (DPPH ), N,N-dimethyl-p-phenylenediamine (DMPD + ), and 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS + ) scavenging activity assays. When compared with standards (BHA-Butylated hydroxyanisole, RUT-Rutin, and TRO-Trolox), it was observed that especially XIII and XIV which include methoxy groups at the o- and m- positions, respectively, had effective activities.
Keywords: Computational chemistry; Methoxy-cinnamic acid; Antioxidant properties; Density functional theory; ,3,4-Thiadiazole; Radical scavenging activities